Low paraspinal lean muscle mass is an independent predictor of adjacent vertebral compression fractures after percutaneous kyphoplasty: A propensity score–matched case-control study - Cheng, Yunzhong; Yang,, Honghao; Hai, Yong; Liu, Yuzeng; Guan, Li; Pan, Aixing; Zhang, Yaosheng (Frontiers in Surgery, 2022)
This study investigated the relationship between paraspinal lean muscle mass and adjacent vertebral compression fracture (AVCF) after percutaneous kyphoplasty (PKP) for osteoporotic vertebral compression fracture (OVCF). 272 patients undergoing two consecutive single-level PKP from 2017 to 2019 were included. 42 patients who met the inclusion and exclusion criteria were selected as AVCF group, and 42 propensity score-matched patients were selected as control group. There were 10 males and 32 females in each group; the ages were 75.55 ± 5.76 years and 75.60 ± 5.87 years, respectively. All patients underwent preoperative lumbar MRI. The total cross-sectional area (CSA), functional cross-sectional area (FCSA), cross-sectional area of vertebra index (CSA-VI), functional cross-sectional area of vertebra index (FCSA-VI) of the multifidus (MF), erector spinae (ES), psoas (PS), and paravertebral muscles (PVM) were measured. Other related parameters included preoperative bone mineral density (BMD), kyphotic angle (KA), anterior-to-posterior body height ratio (AP ratio), vertebral height restoration, and cement leakage into the disc. Logistic regression analysis was performed to find independent risk factors for AVCF using the parameters that were statistically significant in univariate analysis. At L3 and L4 levels, the mean CSA, FCSA, and FCSA-VI of MF, ES, PVM and PS were significantly lower in the AVCF group. DeLong test indicated that the AUC of ES (0.806 vs 0.900) and PVM (0.861 vs 0.941) of FCSA-VI at L4 level were significantly greater than L3 level. In AVCF group, patients had a significantly lower BMD (93.55 ± 14.99 HU vs. 106.31 ± 10.95 HU), a greater preoperative KA (16.02° ± 17.36° vs. 12.87° ± 6.58°), and a greater vertebral height restoration rate (20.4% ± 8.1% vs. 16.4% ± 10.0%, p = 0.026). Logistic regression analysis showed that PVM with lower FCSA-VI at L4 level (OR 0.830; 95% CI 0.760-0.906) and lower BMD (OR 0.928; 95% CI 0.891-0.966) were independent risk factors for AVCF after PKP. Low paraspinal lean muscle mass is an independent risk factor for AVCF after PKP. Surgeons should pay attention to evaluate the status of paraspinal muscle preoperatively. Postoperative reasonable nutrition, standardized anti-osteoporosis treatment, and back muscle exercise could reduce the incidence of AVCF.